Mapping immune trajectories from Helicobacter pylori gastritis to gastric cancer - Song, Yi; Qiu, Jie; Wu, Jingyue; Liu, Wenqi; Wu, Qiang (Frontiers in Immunology, 2025)
Helicobacter pylori-associated gastric tumorigenesis is typically staged by histopathology, yet clinical decisions often hinge on immune dynamics that histology alone cannot resolve. This mini review introduces a phase-specific “immune snapshot” framework that integrates three elements—who is present in the microenvironment, how key circuits are engaged, and where these features reside—to track immune trajectories across chronic gastritis, atrophy with intestinal metaplasia, and dysplasia or early cancer. Rather than cataloging markers, we emphasized a practical approach that maps compact tissue and fluid assays to decision points, including when to normalize stroma and vasculature, when to prime antigenicity, and when to deploy checkpoint blockade. The novelty lies in linking stage-aware immune states to actionable sequencing of interventions and to risk-adapted surveillance intervals. By complementing histopathology with dynamic, mechanism-informed readouts that are feasible in routine practice, the framework aims to identify reversible barriers, clarify timing, and improve the effectiveness of prevention and early immunotherapy.